Oral health promotion in primary schools in Mofolo, Soweto - Nakaziba-Ouma, Ann Martha (My University, 2008)
The oral health knowledge, attitudes and practices of primary school children and teachers in Mofolo, Soweto were determined. The enabling and inhibiting factors for oral health promotion in the school environment were also assessed. The aim of the study was to determine if there was any difference in knowledge, attitudes and, practices in learners and teachers and their environment at schools that were exposed to a preventive, educational and tooth brushing programme and those learners and teachers that were not exposed to the programme. Three hundred and thirty-six primary school children six to twelve years of age from four primary schools in Mofolo, i.e. Itekeng, Vukani, Emsebeni and Tshedimoso completed questionnaires. Itekeng and Vukani primary schools were part of an existing tooth brushing, educative and preventive programme, and Emsebeni and Tshedimoso primary schools were not. Four focus group discussions (one from each school) were held with regard to knowledge of oral health and hygiene and the school environment. Seven teachers from two of the four schools and eight teachers from each of the other two schools attended the discussions. Both the learners and teachers at all the schools had little knowledge of dental care, like tooth brushing with fluoridated toothpaste. Frequency of brushing was poor. Most of the learners (61 percent) for the exposed learners and 50 perecent from the unexposed learners reported brushing their teeth once a day. Dietary habits of the learners revealed a high consumption of sugary snacks in between meals and sugar. Fifty-five percent of the exposed learners bought sweets and cakes and 56 percent of the unexposed learners bought fizzy drinks and fruit juices at school. Forty-six percent of the exposed and 58 percent of the unexposed learners said they took more than three spoons of sugar with their breakfast. . Utilisation of primary dental health services in the community by both teachers and learners was poor. More learners from the exposed schools (97 percent) than the unexposed (82 percent) had been to a dentist because they had a toothache. Only 1 percent from the exposed schools and 8 percent from the unexposed had been for a routine check up. Learners from both school categories and teachers had no knowledge of fluoride or benefits of water fluoridation. Over 98 percent of learners from both school categories had never heard of fluoride. The teachers believed it was their responsibility to teach learners and parents about oral health and showed willingness to participate in oral health promotion programmes. The main source of oral health knowledge among the learners was home. Several inhibiting factors to oral health promotion like poverty, lack of adequate oral health knowledge and poor school environment were identified in all the schools.There was no school policy regarding oral health promotion In conclusion, there were no significant differences in the reported knowledge, attitudes and practices between the learners and teachers from the two schools that were part of the preventive, educational and brushing programme and those from the other schools that were not part of the programme. This therefore shows that while preventive and educational programmes are an important component of oral health promotion, they are not adequate in changing knowledge, attitudes and oral health practices.
Keywords: oral health promotion; primary schools; Soweto